Female Board Representation and Corporate Acquisition Intensity - CHEN, Guoli (Institutional Knowledge at Singapore Management University, 2016)
This study examines the impact of female board representation on firm-level strategic behavior within the domain of mergers and acquisitions (M&A). We build on social identity theory to predict that greater female representation on a firm's board will be negatively associated with both the number of acquisitions the firm engages in and, conditional on doing a deal, acquisition size. Using a comprehensive, multi-year sample of U.S. public firms, we find strong support for our hypotheses. We demonstrate the robustness of our findings through the use of a difference-in-differences analysis on a sub-sample of firms that experienced exogenous changes in board gender composition as a result of director deaths